2022
DOI: 10.1136/jmg-2022-108727
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of theZMYND15gene in a cohort of infertile Chinese men reveals novel mutations in patients with teratozoospermia

Abstract: BackgroundThe information of ZMYND15 in human reproduction is very limited, resulting in the unclear link between ZMYND15 variants and male infertility.MethodsWhole exome sequencing and Sanger sequencing to identify the potential pathogenic variation of ZMYND15 in infertile men, Papanicolaou staining and electron microscopy to investigate the spermatozoa morphology, western blotting and immunofluorescence staining to confirm the pathogenicity of the identified variants, and proteomic analysis and coimmunopreci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…10,46 Previous studies have proved that ZMYND15 mediates spermatogenesis by interacting with DPY19L2, AKAP4, and FSIP2 and regulating the expression of SPATA33. 9 Therefore, we speculated that sodium arsenite downregulates Spaca1, Dpy19l2, Odf1, Akap4, Col1a1, Adam10, Odf2, Akap3, and Fsip2 by reducing the expression of testis-specific protein ZMYND15, then induces the lesion of sperm quality in rats, causes oligospermia or asthenospermia (Scheme 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,46 Previous studies have proved that ZMYND15 mediates spermatogenesis by interacting with DPY19L2, AKAP4, and FSIP2 and regulating the expression of SPATA33. 9 Therefore, we speculated that sodium arsenite downregulates Spaca1, Dpy19l2, Odf1, Akap4, Col1a1, Adam10, Odf2, Akap3, and Fsip2 by reducing the expression of testis-specific protein ZMYND15, then induces the lesion of sperm quality in rats, causes oligospermia or asthenospermia (Scheme 1).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 A cohort study of infertile study has found novel mutations of ZMYND15 in patients with teratozoospermia. 9 ZMYND15 deletion in infertile patients downregulates protein expression of SPACA1, DPY19L2, ODF1, ODF2, AKAP4, AKAP3, COL1A1, FSIP2, and ADAM10, which are involved in sperm head development, flagellation and spermatogenesis. 10 Moreover, ZMYND15 has been proven to be a transcriptional repressor via binding with histone deacetylase enzymes (HDAC1, HDAC3, HDAC6) to regulate the expression of haploid genes including Prm1, Tnp1, Spem1, and Catpser3 during spermatogenesis.…”
mentioning
confidence: 99%
“…A homozygous loss-of-function mutation in the zinc finger MYND-type containing 15 ( ZMYND15 ) gene was found in recent research employing WES. It has been demonstrated that the lack of ZMYND15 produces nonobstructive azoospermia and severe oligozoospermia [ 59 ]; additionally, another research suggests that it may potentially be linked to teratozoospermia [ 60 ]. ZMYND15 has also been described as a switch for haploid gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies reported that mutations on DNAH1, SPEF2, and SEPT12 were correlated with sperm tail anomalies ( 51 - 53 ). Patients who harbor a pathogenic variant of ZMYND15 are also found to have abnormalities in sperm morphology based on sequencing analysis of 227 infertile men in China ( 54 ).…”
Section: Evidence Synthesismentioning
confidence: 99%